Individual vessels, individual burials?: new evidence on early Neolithic funerary practices on the Iberian Peninsula’s Western façade - Cardoso, João Luís (2022)
Early Neolithic funerary practices and the meaning of complete ceramic vessels found isolated are poorly researched topics in western Iberia. However, recent archaeological salvage excavations at Armazéns Sommer and Palácio Ludovice in Lisbon have revealed individual burial pits of male individuals laid in a foetal position and directly associated with necked vessels. These discoveries suggest that finds of isolated vessels, known since the beginning of the twentieth century in Portugal and usually found fortuitously apparently without archaeological context, may also have originally belonged to similar burials, unnoticed by their finders. This hypothesis opens new perspectives for the interpretation of such finds, which are inventoried in the present article.